N-2 Contingency Analysis of an IEEE 14 bus system using MI Power - Vamshi Ram, B.; Upadhyay, Poonam; Radhika, G. (International Journal of Engineering and Technology, 2018)
Nowadays multiple outage contingencies are important for the way the transmission network is used in the deregulated environment. With the increasing load demand and to operate economically, the transmission network is heavily stressed.Â  In this paper, N-2 contingency analysis of an IEEE 14 bus system has been done using MiPower software. Contingency analysis is done for all the possible combinations of N-2 outages of the system using Fast Decoupled load flow method. Real performance index and Voltage performance index are calculated and they are added to give performance index (PI) value to rank the severity of the line outages. Load flow analysis has been done for the severe contingency case.Â Â